Tekst infirmeryjny albo topografia doświadczenia medycznego - Boruszkowska, Iwona (Przestrzenie Teorii, 2018)
The article is a theoretical proposition for a new research category applied to descriptions of diseases within cultural texts. The author proposes a category tying together spatiality and disease, hence the concept of infirmary, which testifies to the complex relationships between space and the experience of illness, or more generally, medical experience, or between the place and the existence of a diseased person, the topography of medical experience. The word „infirmary” will at first glance evoke images of sickbay, i.e. the place for individuals suffering from a medical condition, where they are provided with treatment, and the locus of norm-transgression (that is to say, the norms of the sane society), as well as of stigmatization practices concerning the individual transgressors or deviants, and also of whatever actions are performed on those very individuals (for example, at the hands of doctors or medical personnel). In a nutshell, the concept will evoke all the forms of experience connected with health, disease, treatment practice (both in terms of those providing treatment and those being treated). The infirmary text will be a concept bringing together the narratives of a specific medical experience and the place/space, merging the discourse of disease (but also of health) with a spatial perspective. When speaking of infirmary text, we enter a very broad and multidimensional area situated between literature and medicine. An infirmary text is not limited to all spatial narratives concerning medical experiences, but also touches on extreme emotional experience (the power of affect), the diseases of soma and psyche, the medical institutions and the professional and social roles within their premises, the histories of diseases (especially in the form of autobiographical narratives), affective constructs in which emotions carry the role of „playing the part” of the world and constituting identities.